2016
DOI: 10.1016/j.gpb.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gene Expression Analysis of Mouse and Human Cardiac Maturation

Abstract: Understanding how human cardiomyocytes mature is crucial to realizing stem cell-based heart regeneration, modeling adult heart diseases, and facilitating drug discovery. However, it is not feasible to analyze human samples for maturation due to inaccessibility to samples while cardiomyocytes mature during fetal development and childhood, as well as difficulty in avoiding variations among individuals. Using model animals such as mice can be a useful strategy; nonetheless, it is not well-understood whether and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 28 publications
(40 reference statements)
0
39
0
Order By: Relevance
“…This suggests that the machinery needed for CM maturation might be conserved in rodents and humans. In fact, although rodents have a shorter lifespan, comparative transcriptional analyses revealed that genes involved in mouse CM maturation are similarly regulated during human heart maturation (Uosaki and Taguchi, 2016). It will be interesting to test if hPSC-CMs can also be matured in larger animal models.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the machinery needed for CM maturation might be conserved in rodents and humans. In fact, although rodents have a shorter lifespan, comparative transcriptional analyses revealed that genes involved in mouse CM maturation are similarly regulated during human heart maturation (Uosaki and Taguchi, 2016). It will be interesting to test if hPSC-CMs can also be matured in larger animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the genes involved in human cardiomyocytes maturation is still an ongoing process. But the overall expression pattern of maturation-related genes identified in mice and humans are mostly similar (DeLaughter et al, 2016;Uosaki and Taguchi, 2016). Isoform transitions of sarcomeric genes occur from fetal to adult period.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Thereby, data sets of several knock-out and knock-in mouse models [13][14][15] have been useful to validate data. Differences between mouse and human signaling cascades have been observed in several cell types including platelets [16][17][18]. Therefore, systematic analyses of mouse and human platelet signaling cascades are required to estimate limitations of transferability of generated results and stress human speci cs including potential therapeutic targets.…”
Section: Methods Of Bioinformatics Have Already Been Used To Simulatementioning
confidence: 99%